Role of Imaging in Diagnosis of Rare Case of Hodgkin's Lymphoma (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2025)
Hodgkin's lymphoma (HL) is an uncommon but highly curablepediatric malignancy, rarely diagnosed in children below ten years of age due to its subtle, nonspecific clinical presentation. We report a rare case of classical HL in a 7- year-old male presenting with low-grade fever, dry cough, pallor, and cervical lymphadenopathy. The patient had been empirically started on anti-tubercular therapy without improvement. Clinical evaluation revealed hepatosplenomegaly and widespread lymphadenopathy. Chest X-ray and abdominal ultrasonography weresuggestive of a mediastinal mass and multiple splenic lesions. Contrast-enhanced computed tomography (CECT) confirmed a large, homogeneously enhancing mediastinal mass with vascular encasement and extensive abdominal nodal involvement. Based on imaging and clinical features, the case was classified as stage IVB Hodgkin lymphoma per Lugano classification. Histopathological confirmation was achieved through lymph node biopsy revealing Reed-Sternberg cells. Multimodal imaging played a pivotal role not only in initial detection and staging butalso in identifying biopsy sites and guiding therapeutic decisions. This caseunderscores the diagnostic value of integrated imaging-including ultrasound, CECT, and PET/CT-in accurately evaluating pediatric lymphomas, especially in atypical age groups. It also highlights the risk of misdiagnosis and treatment delays when empirical therapies like ATT are initiated without confirmatory histology. Prompt imaging and tissue diagnosis are vital to ensure timely intervention and optimal outcomes. A multidisciplinary approach, integrating radiologic, pathologic, and clinical expertise, is crucial for managing such rare pediatric malignancies and improving long-term prognosis.